Value of Carbohydrate Antigen 19-9 in Predicting Response and Therapy Control in Patients with Metastatic Pancreatic Cancer Undergoing First-Line Therapy - Pelzer, Uwe; Hilbig, Andreas; Stieler, Jens; Sinn, Marianne; Bahra, Marcus; Dörken, Bernd; Riess, Hanno (Frontiers in Oncology, 2013)
Background: Serum carbohydrate antigen 19-9 (CA 19-9) has been shown to be a sensitive and specific serum marker for pancreatic cancer. Little has been published about correlations between baseline CA 19-9 level or changes to CA 19-9 level and median overall survival (mOS). Its impact on monitoring treatment efficacy remains under discussion, however. Methods: CA 19-9 serum level was measured in 181 consecutive patients with advanced pancreatic cancer (APC) being treated with gemcitabine-based first line chemotherapy. We separated the patients into several groups depending on baseline CA 19-9 levels and the CA 19-9 response after 6 to 8 weeks of treatment. Evaluations were made using SPSS 19.9. Results: Median baseline CA 19-9 level was 1,493 U/ml (range 40-1,043,301). Patients with baseline CA 19-9 ≤1,000 U/ml had a mOS of 14.9 months [95%CI: 11.36:18.44], whereas patients with CA 19-9 >1,000 U/ml had a mOS of 7.4 months ([95%CI: 5.93:8.87] p<0.001, HR 2.12). With regard to the change in CA 19-9 after 6 to 8 weeks of treatment: patients with increased CA 19-9 levels had a mOS of 8.1 months, those with stabilized CA 19-9 levels 11.6 months, and those with decreased CA 19-9 levels 11.1 months (p<0.019). Conclusions: CA 19-9 levels can separate patients with differing mortality risks at baseline. Patients with stabilization or high response of CA 19-9 after 6 to 8 weeks of treatment had no significant differences in survival rates, whereas patients with increased CA 19-9 had significantly lower survival rates, indicating an early treatment failure.